Molecular dynamic simulation reveals the inhibiting impact of Rhein on wild-type and P29S-mutated Rac1 - Etebar, Negar; Hamidi, Seyed Hootan; Naderpour, Saghi; Abouali, Omar; Hamidi, Seyedeh Harir; Hajipour-Verdom, Behnam; Zali, Alireza; Alipour, Mozhgan; Rahimzadegan, Milad (Frontiers in Molecular Biosciences, 2024)
Ras-related C3 botulinum toxin substrate 1 (Rac1) is a small GTPase belonging to the Rho family acting as a binary molecular switch regulating a number of cellular functions including cell adhesion and migration. Malfunctions due to the P29S mutation in Rac1 increase the stability of the activated form of Rac1. This sustained activation can drive aberrant cellular processes associated with cancer, such as cell proliferation, survival, and migration. Therefore, finding an inhibitor that can inhibit mutant form of the protein is very important. On the other hand, Rhein, a natural compound with diverse pharmacological properties, has been studied in relation to Rac1. While specific interactions between Rhein and Rac1 have not been examined. So, in this study, we investigated the potential of Rhein, a natural compound, as a Rac1 inhibitor in two forms wild type and P29S mutation using molecular dynamics simulations. Results indicated that P29S mutation led to structural changes in Rac1 protein that results in greater accessibility of the Rhein to the active site. Also binding energy of Rhein to mutant Rac1 was more negative than native protein. Therefore, it seems that the Rhein has a better inhibitory effect on the P29S mutated form of the Rac1 protein.